Dear Tiny Heart : the Letters of Jane Heap and Florence Reynolds. - Baggett, Holly A., 1957- (Cutting Edge: Lesbian Life and Literature Series., 2000)
Writer, artist, Manhattan gallery owner, and co-editor of the Little Review, Jane Heap was one of the most dynamic figures of the international avant garde, creating a life that defined the "modernist experience" as a syncretic one. Deliberately seeking a low profile throughout her life, Heap has frustrated many scholars interested in her personal life and the extraordinarily vital period in which she lived. Through her correspondence, Heap here reveals her intimate self as well as her more public, creative relationships with some of the legends of modern art, literature, and spirit.